Local center-projective spaces and connectivities of a differentiable manifold - Lemlein, V. G. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Г. Лемлейн. Локальные центро-проективные пространства и связности в дифференцируемом многообразииV. G. Lemlein. Lokalinės centro-projektyvinės erdvės ir diferencijuotinės daugdaros sąryšiai